Working back to normality : the patient experience of wrist fracture : a thesis presented in partial fulfilment of the requirements of the degree of Master of Arts in Nursing at Massey University - Potiki, Jane (Massey University, 2001)
This qualitative descriptive study explored the patient experience of wrist fracture, which was treated within an emergency department setting, with the patient not requiring hospital admission. Ten participants were interviewed about their experiences of wrist fracture, with data being analysed using constant comparative analysis. The experience of wrist fracture has not previously been explored from a patient perspective, although the medical treatment of this injury has been well documented. The findings of this study have provided some enlightenment about the way patients live through an acute injury, coping with treatment, symptoms and disability. The impact of the injury upon the individual's lifestyle was substantial, even though this is medically classed as a 'minor injury'; with some participants' having developed long term complications. Participants had contact with health workers in many circumstances, and they had both positive and negative effects on the participant's experience of injury and treatment. The categories identified in this study were Getting Through Injury, Putting Life on Hold, and Being in their Hands. Working Back to Normality was identified as the core category, with participants working towards this goal from the outset of their injury experience. As a result of this study, it is clear that nursing practice needs to focus upon developing positive relationships with patients; to address issues related to pain management, before and during treatment; and to improve patient preparation for treatment and education. It also needs to be emphasised that the relationship with patients who have experienced wrist fracture does not end with the patient going home. For patients, working back to normality is an ongoing process which commences at the time of injury, and which may last for several months, or years.
Keywords: Wrist fractures -- Patients